Gambel’S Quail: A History of Research and Management at the Oracle Junction Study Area in Arizona - Johnathan C. O'Dell; Scott Christopher McAdams (National Quail Symposium Proceedings, 2017)
We analyzed current as well as historic call-count survey data, check station harvest data, season length, winter precipitation, and daily bag limits in the Oracle Junction Study Area, Arizona to verify factors affecting annual Gambel’s quail (Callipepla gambelii) harvest. Gambel’s quail is the only one of the 9 species of wild gallinaceous game birds found in Arizona endemic to the Sonoran Desert. Oracle Junction has been of particular importance to quail hunters, scientists, researchers, and managers because it has a consistent history of call-count surveys, open hunting seasons, hunter-harvest check stations, and available precipitation data. Oracle Junction provides a valuable ‘experiment’ of Gambel quail harvest management in Arizona.
Keywords: Arizona; call-count surveys; Callipepla gambelii; Gambel’s quail; Oracle Junction